Comparison of Clinical Severity Improvement Degree between Acute Thrombotic Stroke Patients with Low and High Matrix Metalloproteinase-9 Levels - Muhamad Hamdan1, Hendro Susilo, Paulus Sugianto1, A. Firdaus Sami1, Mohammad Saiful Ardhi1, Sita Set (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Stroke is a cause of disability and dependency in both humanity and economic. Studies on the association of Matrix metallopeptidase 9 (MMP-9) levels with improved clinical severity are currently limited. Objectives: To determine the improvement of clinical severity in acute thrombotic stroke patients with high and low MMP-9 levels. Methods: Patients acute thrombotic stroke were grouped into low and high MMP-9 levels. MMP-9 levels were considered low when <840 ng/mL and high when ?840 ng/mL. Clinical severity improvement was assessed using the ?NIHSS scale. Results: Eighty subjects were enrolled that consists of clinical severity improved patients with lower MMP9 (37.9%) that higher than high MMP-9 (21.6%). This difference was not statistically significant (p = 0.115). Conclusion: There was no difference in clinical severity improvement in patients with acute thrombotic stroke with low MMP-9 levels in blood serum compared to high MMP-9 levels.